A catalog of early-type emission-line stars and Hα line profiles from LAMOST DR2. (September 2016) - Hou, Wen; Luo, A-Li; Hu, Jing-Yao; Yang, Hai-Feng; Du, Chang-De; Liu, Chao; Lee, Chien-De; Lin, Chien-Cheng; Wang, Yue-Fei; Zhang, Yong; Cao, Zi-Huang; Hou, Yong-Hui
Abstract: We present a catalog including 11 204 spectra of 10 436 early-type emission-line stars from LAMOST DR2, among which 9752 early-type emission-line spectra are newly discovered. For these early-type emission-line stars, we discuss the morphological and physical properties of their low-resolution spectra. In this spectral sample, the Hα emission profiles display a wide variety of shapes. Based on the Hα line profiles, these spectra are categorized into five distinct classes: single-peak emission, single-peak emission in absorption, double-peak emission, double-peak emission in absorption, and P-Cygni profiles. To better understand what causes the Hα line profiles, we divide these objects into four types from the perspective of physical classification, which include classical Be stars, Herbig Ae/Be stars, close binaries and spectra contaminated by HΠ regions. The majority of Herbig Ae/Be stars and classical Be stars are identified and separated using a ( H-K, K-W1 ) color-color diagram. We also discuss 31 binary systems that are listed in the SIMBAD on-line catalog and identify 3600 spectra contaminated by HΠ regions after cross-matching with positions in the Dubout-Crillon catalog. A statistical analysis of line profiles versus classifications is then conducted in order to understand the distribution of Hα profiles for each type in our sample. Finally, we also provide a table of 172 spectra with FeΠ emission lines and roughly calculate stellar wind velocities for seven spectra with P-Cygni profiles.